2012
DOI: 10.1111/j.1600-079x.2012.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin‐rich transgenic rice plants exhibit resistance to herbicide‐induced oxidative stress

Abstract: To examine whether melatonin-rich plants can defend against oxidative stress, we subjected melatonin-rich transgenic (MRT) rice plants to the singlet-oxygen-generating herbicide butafenacil. Both MRT and transgenic control (TC; expressing the vector only) rice seeds germinated and grew equally well in continuous dark on half-strength Murashige and Skoog (MS) medium containing 0.1 μm butafenacil. However, after transferring the seedlings to light, the TCs rapidly necrotized, whereas the MRT seedlings showed res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
188
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(194 citation statements)
references
References 44 publications
6
188
0
Order By: Relevance
“…Transgenic rice plants rich in MEL were more resistant to butafenacil, a herbicide which induces oxidative stress (Park et al 2013b). Due to antioxidant properties, MEL protected the roots of barley from the damaging effects of NaCl, ZnSO 4 and H 2 O 2 (Tan et al 2010).…”
Section: Antioxidative Role Of Melmentioning
confidence: 99%
“…Transgenic rice plants rich in MEL were more resistant to butafenacil, a herbicide which induces oxidative stress (Park et al 2013b). Due to antioxidant properties, MEL protected the roots of barley from the damaging effects of NaCl, ZnSO 4 and H 2 O 2 (Tan et al 2010).…”
Section: Antioxidative Role Of Melmentioning
confidence: 99%
“…It seems that this indoleamine plays a significant role in plant stress defense. It was observed that melatonin-rich plant species showed higher capacity for tolerance of unfavorable conditions (Park et al 2013;Bajwa et al 2014;Zhang et al 2015). Moreover, exogenously applied melatonin improved resistance to Marssonina apple blotch caused by Diplocarpon mali-dangerous pathogen that generates losses in the cultivation of apples (Yin et al 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Its levels vary between species, ranging from a few picograms to micrograms per gram of tissue [11]. Melatonin is implicated in pleotropic functions in plants as a potent antioxidant [12], growth promoter [13,14], flowering and senescence inhibitor [15,16], and protector against various abiotic and biotic stresses such as salt, heavy metals, temperatures, drought, and pathogens [17][18][19][20][21][22]. These physiological functions of melatonin are closely associated with a diverse array of gene regulation in response to melatonin [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%